The frailty of models, the new era, or a rotten world of consumers' financial behaviour? - Anna Warchlewska (Central European Economic Journal (CEEJ), 2024)
The aim of the article is to analyse the structure of consumer behaviour models and their applications to financial behaviour. The paper is theoretical in nature, examining generational breakdowns and selected trends in consumer behaviour. An analysis of the 'rules' significant for types of consumer behaviour is conducted. Despite recently intensified theoretical and empirical analysis of consumer behaviour, a coherent research approach that integrates the issue of consumer behaviour with the specificities of the financial-services market has not yet been developed. Models remain frail, their functionality is still insufficient, and their applicability is constantly being altered by influences on consumer behaviour, including macro and microeconomic factors and the influence of scientific fields such as economics, sociology, psychology, management and anthropology. This article attempts to create a model that takes into account the general factors adopted in models constructed so far, along with the assumption that economic, cultural, social, personal, experiences, and other factors play a role in shaping and stimulating at least five variables: type of consumer from a particular generation (Cy); type of financial products and services (Xy); motivation (My); capacity (Capy); and opportunities (Oy).
Keywords: A14; D10; G4; 330; consumer behaviour models; generations; personal finance; behavioural trends